A potential adverse role for leptin and cardiac leptin receptor in the right ventricle in pulmonary arterial hypertension: effect of metformin is BMPR2 mutation-specific - Talati, Megha; Brittain, Evan; Agrawal, Vineet; Fortune, Niki; Simon, Katie; Shay, Sheila; Zeng, Xiaofang; Freeman, Michael L.; West, James; Hemnes, Anna (Frontiers in Medicine, 2023)
Introduction: Pulmonary arterial hypertension is a fatal cardiopulmonary disease. Leptin, a neuroendocrine hormone, released by adipose tissue has a complex relationship with cardiovascular diseases including PAH. Leptin is thought to be an important factor linking metabolic syndrome and cardiovascular disorders. Given the published association between metabolic syndrome and RV dysfunction in PAH, we sought to determine the association between leptin and RV dysfunction. We hypothesized that in PAH-RV, leptin influences metabolic changes via leptin receptors, which can be manipulated by metformin. Methods: Plasma leptin was measured in PAH patients and healthy controls from a published trial of metformin in PAH. Leptin receptor localization was detected in RV from PAH patients, healthy controls, animal models of PH with RV dysfunction before and after metformin treatment, and cultured cardiomyocytes with two different BMPR2 mutants by performing immunohistochemical and cell fractionation studies. Functional studies were conducted in cultured cardiomyocytes to examine the role of leptin and metformin in lipid-driven mitochondrial respiration. Results: In human studies, we found that plasma leptin levels were higher in PAH patients and moderately correlated with higher BMI, but not in healthy controls. Circulating leptin levels were reduced by metformin treatment and these findings were confirmed in an animal model of RV dysfunction. Leptin receptor expression was increased in PAH-RV cardiomyocytes. In animal models of RV dysfunction and cultured cardiomyocytes with BMPR2 mutation we found increased expression and membrane localization of leptin receptor. In cultured cardiomyocytes with BMPR2 mutation, leptin moderately influences palmitate uptake possibly via CD36 in a mutation-specific manner. Further, in cultured cardiomyocytes, Seahorse XFe96 Extracellular Flux Analyzer and gene expression data indicate that leptin may not directly influence lipiddriven mitochondrial respiration in BMPR2 mutant cardiomyocytes. However, metformin alone or when supplemented with leptin can improve lipid-driven mitochondrial respiration in BMPR2 mutant cardiomyocytes. The effect of metformin on lipid-driven mitochondrial respiration in cardiomyocytes is BMPR2 mutation-specific.In PAH increased circulating leptin can influence metabolic signaling in RV cardiomyocytes via leptin receptor; in specific, it may alter lipid-dependent RV metabolism in combination with metformin in a mutation-specific manner and warrants further investigation.